Pembagian Kerja Berdasarkan Gender dalam Pengelolaan Agroforestri di Hulu DAS Citarum - Salma Rizkya Kinasih; Indri Wulandari (Umbara, 2021)
This study discusses gender division of labor in agroforestry at Tarumajaya Village, upstream of Citarum Watershed. This study aims to describe the division of labor mechanism of agroforestry farmers based on the anthropology of gender perspective. The manifestation of gender can be seen from the mechanism of division labor on every kind of land-use system. Agroforestry is an intensive land-use system that combines crops, woods, and/or livestock in one intensive land to obtain economic-ecology harmonization. Agroforestry was introduced by the government through a top-down approach, by Peraturan Presiden No. 15/2018 about the Acceleration of Pollution Control and Damage to the Citarum River Basin, which is used to conserve the Citarum Watershed. Unfortunately, agroforestry had unfavorable condition due to the clash with crops habits and subsistence economic needs. This research applied ehnographic methods and the data were collected through literature study, observation, and in-depth interview. The data were analyzed using Gender Harvard Analytical Framework. This study found that the division of labor in agroforestry households is negotiable. Men and women have the opportunities to work together in the system. However, gender blind introduction of agroforestry only made women as cheap wage labor. They are being subordinated and alienated by the system. They don’t have equal access and control to the technology, information, and market. These problems occur because gender intersects with various factors such as culture and religion, demography, economy, formal law, social class, and politics. Therefore, agroforestry needs to take a gender approach to get optimum results.